2009
DOI: 10.1111/j.1365-2389.2009.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of organic and conventional management on soil aggregate stability using X‐ray computed tomography

Abstract: Soil aggregate stability is an important measure for assessing soil structural quality. Here we compare stable and unstable soil aggregates from organically and conventionally managed soils that have similar organic matter contents to determine the role of management in aggregate stability. Aggregate stability was determined by slaking, which proved to be an accurate estimator of the rate of aggregate turnover. The results indicate that, in soil aggregates released by slaking, the organic matter is held in agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 24 publications
1
53
1
Order By: Relevance
“…It is likely that once the macro-aggregates break into micro-aggregates, they do so along the pores >15 μm, especially along the 15 to 60 μm micro-cracks. Even though no direct relationships between aggregate pore characteristics and aggregate stability were observed previously (De Gryze et al, 2006;Papadopoulos et al, 2009), however, as pointed by Bresson and Moran (2004), such relationships might be a complex function where aggregates' physical characteristics are related to pores of some but not other sizes. Our results appear to support this notion.…”
Section: Numbers Of Pore Voxelsmentioning
confidence: 86%
See 2 more Smart Citations
“…It is likely that once the macro-aggregates break into micro-aggregates, they do so along the pores >15 μm, especially along the 15 to 60 μm micro-cracks. Even though no direct relationships between aggregate pore characteristics and aggregate stability were observed previously (De Gryze et al, 2006;Papadopoulos et al, 2009), however, as pointed by Bresson and Moran (2004), such relationships might be a complex function where aggregates' physical characteristics are related to pores of some but not other sizes. Our results appear to support this notion.…”
Section: Numbers Of Pore Voxelsmentioning
confidence: 86%
“…Peth et al (2008) reported smaller nodal pore volumes and shorter path lengths in 5 mm aggregates from CT than from long-term grassland. Papadopoulos et al (2009) noted diff erences in pore shapes in 5 mm aggregates from conventional and organic management. We hypothesize that diff erences in the intensity of soil disturbance, frequencies of wetting/drying patterns, amounts of biomass inputs, microbial and faunal activities in soils under conventionally plowed agricultural management as compared to NT and to undisturbed nonagricultural NS land use may lead to substantial diff erences in the intra-aggregate pore characteristics, including porosity, pore size distributions, and heterogeneity in pore distribution patterns.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The soil particles have different arrangement and structure, varying, thus, the form (ELLIOT et al, 2010;PAPADOPOULOS et al, 2009), the length (WANG et al, 2012), the width and the tortuosity (UDAWATTA et al, 2008). Therefore, the arrangement of the soil particles determines the quantity of existing pores.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several studies have documented these anthropogenic effects on soil physical properties using x-ray CT systems (Olsen and Børresen, 1997;Gantzer and Anderson, 2002;Munkholm et al, 2003;Papadopoulos et al, 2009;Garbout et al, 2013). Gantzer and Anderson (2002) indicated that important features of soil structure are the number and size of macropores, which include tillage-induced structures, wormholes, and root channels.…”
mentioning
confidence: 99%